2018
DOI: 10.1186/s12974-018-1269-3
|View full text |Cite
|
Sign up to set email alerts
|

K284-6111 prevents the amyloid beta-induced neuroinflammation and impairment of recognition memory through inhibition of NF-κB-mediated CHI3L1 expression

Abstract: BackgroundAlzheimer’s disease, which is pathologically characterized by an excessive accumulation of amyloid beta (Aβ) fibrils, is a degenerative brain disease and the most common cause of dementia. In a previous study, it was reported that an increased level of CHI3L1 in plasma was found in AD patients. We investigated the inhibitory effect of 2-({3-[2-(1-cyclohexen-1-yl)ethyl]-6,7-dimethoxy-4-oxo-3,4-dihydro-2-quinazolinyl}sulfanyl)-N-(4-ethylphenyl)butanamide (K284-6111), an inhibitor of chitinase 3 like 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 33 publications
4
67
1
Order By: Relevance
“…Our previous study suggested that K284-6111 could act as an inhibitor of CHI3L1 by directly binding to CHI3L1 [33]. In this study, we also found that administration of K284-6111 markedly attenuated impaired cognitive function and memory in Tg2576 AD mouse model.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our previous study suggested that K284-6111 could act as an inhibitor of CHI3L1 by directly binding to CHI3L1 [33]. In this study, we also found that administration of K284-6111 markedly attenuated impaired cognitive function and memory in Tg2576 AD mouse model.…”
Section: Discussionsupporting
confidence: 74%
“…Pranzatelli et al reported that the CHI3L1 is increased in CSF and serum of in ammatory neurological disorders in children [47]. In our previous study, Aβ-induced AD mouse model showed higher level of CHI3L1 in brain compared to that of controls, and we also demonstrated that CHI3L1-knockdown reduced in ammatory proteins such as iNOS and COX-2 in LPS-stimulated BV-2 cells [33]. Consistent with our previous ndings, the present study showed that overexpression of CHI3L1 increased expression of pro-in ammatory cytokines, Cd86, one of the markers of M1 microglia, and in ammatory proteins in CHI3L1 overexpressing BV-2 cells.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Recently, chitinase 3 like 1 (Chi3L1) expression has been found in a variety of cancer cells such as breast, lung, prostate, colon, rectum, ovary, kidney, glioblastomas, and malignant melanoma (14)(15)(16)(17)(18)(19)(20). We also previously selected 20 chemicals as candidate compounds for the ligand of Chi3L1 by using 3D chemical database analysis with X-ray structure-based virtual screening (21), and G721-0282 was obtained from ChemiDiv Inc. (http://www.chemdiv.com). In the present study, we investigated whether G721-0282, a candidate ligand of Chi3L1 regulates in vitro effects on proliferation, apoptosis, migration, invasion, and colony formation in OS cells, and in vivo anti-tumor effects in a xenograft mouse model.…”
Section: Ivyspringmentioning
confidence: 99%